Effects of different powders on the micro-gap laser welding-brazing of an aluminium-steel butt joint using a coaxial feeding method. (5th November 2016) - Zhang, Yi; Li, Funan; Guo, Guanlin; Wang, Gang; Wei, Haiying
Abstract: Due to the large differences in the physical and chemical properties of aluminium and steel, brittle intermetallic compounds such as Fe-Al form easily when their components are welded together. In this study, a coaxial powder feeding method was used to deliver AlSi12, AlCu5 and ZnAl15 powders for butt laser welding of aluminium 5251 and TG-1 automotive steel with 1 mm thickness under micro-gap conditions. The butt gap was controlled at 40–80 μm in the experiment, and the focus offset was 400–800 μm. Welds filled with AlSi12 powder had high-quality surfaces and no welding spatter. The fusion zone grain structure consisted of Al-Si eutectic structures, and the intermetallic compound (IMC) layer was 4 μm thick. The average IMC layer thickness was 2–6 μm for three filler powders. Si formed compounds FeAl3 Si and Fe0·905 Si0.0905 in the IMC layer, which reduced butt's brittleness. However, chemical reactions of Cu and Zn with Fe and Al, respectively, did not exist in the IMC layer. The tensile strength of welding joint filled with AlSi12 powder was the greatest; it reached 67.6% of that of the aluminium alloy base material. Graphical abstract: Highlights: Laser butt welding of Al/Fe dissimilar metals was performed using a coaxial powder feeding method. Welding process was performed under the micro-gap butt conditions. The tensile strength of the joint with AlSi12 powder reached 67.6% of that of the Al base material. Only element Si was found in IMC layers with AlSi12, AlCu5 and ZnAl15 filler powders respectively.